A New Industry and Tax Base on Taxing Esports in Indonesia - Sung, Ming-Hsi; Umar, Wahyudi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Unlike traditional sports that relies on traditional television broadcasting, esports usually adopts live streaming on internet platforms, such as YouTube, as its medium.Â Through a delicate design of profit sharing, live esports streaming and media have greatly changed the video game industry from sheer family entertainment machine makers into a new frontier of money making sport, and therefore the game players into a profession that may make billion dollars annually. This paper intends to introduce the current situation of esports in Indonesia, asserting the potential to collect tax from live game streamers (Content Creators) and YouTube (Platform), and players from this newly developed sports industry to broaden the tax base in Indonesia.Â This research is a normative legal research. Data collected from books, journals, relevant laws and regulations. The results show that the government should either revise the current tax law and legal design that are obvious out-of-dated and dysfunctional or follow developed countries to have law specifically designed for taxing esports industry and e-economy.